Enhancing Legal Frameworks for the Conservation of Tangible Cultural Heritage in Thailand: Problems and Solutions - Wimonrart Issarathumnoon (SPAFA Journal)
Government agencies in various countries use legal tools to conserve and manage tangible cultural heritage effectively. Laws, measures, and standards ensure operations adhere to conservation principles and maintain consistency. In Thailand, legal tools for protecting tangible cultural heritage have evolved over six decades, particularly under the Ancient Monuments Act. However, these tools are inefficient due to two critical issues. Firstly, there is a lack of comprehensive protection, inconsistent laws, and inadequate enforcement, especially for heritage of low or moderate value, privately owned, or outside protected areas. Secondly, implementation is highly fragmented, involving multiple agencies and resulting in complicated and disjointed operations. Amending each law individually is unlikely to be effective. One of the potential solutions is to create a primary law for the inclusive conservation and management of tangible cultural heritage. This law should harmonise and connect existing laws, addressing all types, values, and forms of tangible cultural heritage regardless of ownership. It is crucial to establish mechanisms that decentralise operations to local levels and encourage participation from various sectors. Moreover, developing conservation standards is essential to ensure the consistent use of these instruments.